Valencene oxidase CYP706M1 from Alaska cedar (Callitropsis nootkatensis). Issue 6 (11th February 2014) - Cankar, Katarina; van Houwelingen, Adèle; Goedbloed, Miriam; Renirie, Rokus; de Jong, René M.; Bouwmeester, Harro; Bosch, Dirk; Sonke, Theo; Beekwilder, Jules
Abstract : (+)‐Nootkatone is a natural sesquiterpene ketone used in grapefruit and citrus flavour compositions. It occurs in small amounts in grapefruit and is a major component of Alaska cedar ( Callitropsis nootkatensis ) heartwood essential oil. Upon co‐expression of candidate cytochrome P450 enzymes from Alaska cedar in yeast with a valencene synthase, a C. nootkatensis valencene oxidase (CnVO) was identified to produce trans ‐nootkatol and (+)‐nootkatone. Formation of (+)‐nootkatone was detected at 144 ± 10 μg/L yeast culture. CnVO belongs to a new subfamily of the CYP706 family of cytochrome P450 oxidases. Abstract : (+)‐Nootkatone is a major sesquiterpene component of Alaska cedar essential oil. Alaska cedar valencene oxidase CYP706M1 was identified and cloned. CYP706M1 catalyses the oxidation of (+)‐valencene in yeast and in vitro . (+)‐Nootkatone was produced at 144μg/L by CYP706M1‐expressing yeast culture. CYP706M1 is the first valencene oxidase from a (+)‐nootkatone producing plant.